The craniomandibular anatomy of the early archosauriform Euparkeria capensis and the dawn of the archosaur skull. Issue 7 (29th July 2020) - Sookias, Roland B.; Dilkes, David; Sobral, Gabriela; Smith, Roger M. H.; Wolvaardt, Frederik P.; Arcucci, Andrea B.; Bhullar, Bhart-Anjan S.; Werneburg, Ingmar
Abstract : Archosauria (birds, crocodilians and their extinct relatives) form a major part of terrestrial ecosystems today, with over 10 000 living species, and came to dominate the land for most of the Mesozoic (over 150 Myr) after radiating following the Permian–Triassic extinction. The archosaur skull has been essential to this diversification, itself diversified into myriad forms. The archosauriform Euparkeria capensis from the Middle Triassic (Anisian) of South Africa has been of great interest since its initial description in 1913, because its anatomy shed light on the origins and early evolution of crown Archosauria and potentially approached that of the archosaur common ancestor. Euparkeria has been widely used as an outgroup in phylogenetic analyses and when investigating patterns of trait evolution among archosaurs. Although described monographically in 1965, subsequent years have seen great advances in the understanding of early archosaurs and in imaging techniques. Here, the cranium and mandible of Euparkeria are fully redescribed and documented using all fossil material and computed tomographic data. Details previously unclear are fully described, including vomerine dentition, the epiptergoid, number of premaxillary teeth and palatal arrangement. A new diagnosis and cranial and braincase reconstruction is provided, and an anatomical network analysis is performed on the skull of Euparkeria and compared with other amniotes. The modular composition of the cranium suggests a flexible skull well adapted to feeding on agile food, but with a clear tendency towards more carnivorous behaviour, placing the taxon at the interface between ancestral diapsid and crown archosaur ecomorphology, corresponding to increases in brain size, visual sensitivity, upright locomotion and metabolism around this point in archosauriform evolution. The skull of Euparkeria epitomizes a major evolutionary transition, and places crown archosaur morphology in an evolutionary context.